APS could potentially activate hepatic insulin signaling in HFD-induced IR mice. (July 2019) - Sun, Jie; Liu, Yan; Yu, Jinhui; Wu, Jin; Gao, Wenting; Ran, Liyuan; Jiang, Rujiao; Guo, Meihua; Han, Dongyu; Liu, Bo; Wang, Ning; Li, Youwei; et al.
Abstract : Astragalus polysaccharide (APS) is the main component of Astragalus membranaceus, an anti-diabetic herb being used for thousands of years in Traditional Chinese medicine (TCM). In this study, we aimed to evaluate the impact of APS on hepatic insulin signaling, autophagy and ER stress response in high-fat-diet (HFD)-induced insulin resistance (IR) mice. APS was intra-gastrically administrated and metformin was used as a control medicine. Apart from monitoring the changes in the important parameters of IR progression, the gene and protein expression of the key factors marking the state of hepatic ER stress and autophagic flux were examined. We found that, largely comparable to the metformin regime, APS treatment resulted in an overall improvement of IR, as indicated by better control of body weight and blood glucose/lipid levels, recovery of liver functions and regained insulin sensitivity. In particular, the excessive and pro-apoptotic ER stress response and inhibition of autophagy, as a result of prolonged HFD exposure, were significantly corrected by APS administration, indicating a switch of the cellular fate in favor of cell survival. Using the HepG2/IR cell model, we demonstrated that APS modulated the insulin-initiated phosphorylation cascades in a similar manner to metformin. This study provides a rationale for exploiting the insulin-sensitizing potential of APS, which has a therapeutic performance almost equivalent to metformin, to enrich our options in the treatment of IR.